Extracting and Retargeting Color Mappings from Bitmap Images of Visualizations - Poco J. (2018)
This work was supported by a Paul G. Allen Family Foundation Distinguished Investigator Award and the Moore Foundation Data-Driven Discovery Investigator program. The second author gratefully acknowledges CONCYTEC for a scholarship in support of graduate studies.